Guidelines For Investing PRG, PRG-HIPC, and CCR Trust Assets. (Policy Papers; Policy Paper ;, 2022)
Guidelines for Investing PRG, PRG-HIPC, and CCR Trust Assets (the "Guidelines"), which were adopted on March 22, 2017, were further amended on January 12, 2022, by the Executive Board of the IMF. The Guidelines establish the investment objectives and policies to guide the investment of assets of the PRG, PRG-HIPC, and CCR Trusts (the "Trusts") which are available for investment under the Trusts' instruments.